Efektivitas Komunikasi Pemasaran Produk Gapoktan Mitra - Distantya Hanifa; Joko Winarno; Suminah Suminah (Jurnal Sosial Ekonomi Pertanian, 2023)
This study aims to describe the effectiveness of product marketing communications and describe variables and analyze the effect of advertising, sales promotion, personal selling (personal selling), direct marketing(direct selling), and word of mouth both simultaneously and partially on the effectiveness of product marketing communications at Roko. Indonesian Farmer Center, Yogyakarta. This study uses a quantitative method with the selection of samples by non-probable sampling. Data were analyzed through descriptive analysis, verification, classical assumption test, and multiple linear regression. The results show the effectiveness of marketing communication for partner Gapoktan products at the Indonesian Farmer Store Yogyakarta Center including the components of knowledge and behavior change as a whole in the high category. The variables of sales promotion, individual selling, direct marketing, and word of mouth have a significant effect on the effectiveness of marketing communication for partner gapoktan products at Toko TaniIndonesia Center Yogyakarta. While the advertising variable has no effect. The value of the coefficient of determination (R2) is 0.874, meaning that 87.4% of the effectiveness of marketing communication for partner gapoktan products at TTIC Yogyakarta can be explained by the variables of advertising, sales promotion, personal selling, direct marketing, and word of mouth.